THE CHARACTERISTICS OF SHRIMP FISHERIES IN KOTABARU, SOUTH KALIMANTAN, INDONESIA - Harlyan, Ledhyane Ika; Setyohadi, Daduk; Tumulyadi, Agus; Sukandar, Sukandar; Maulana, Almaas Zain; Lathif, Adib Hisyam; Fanani, Zainal (Journal of Environmental Engineering and Sustainable Technology, 2024)
The shrimp fishery in Kotabaru, South Kalimantan, is a small-scale fishery that supplies raw materials to PT. Sekar Laut, Tbk, a company specializing in shrimp cracker production for the global market. Despite its significance, limited research has been conducted on the sustainability of this fishery. This study aims to analyze the key characteristics of the shrimp fishery in Kotabaru waters. Data were collected from January to August 2024 in Kotabaru, South Kalimantan, and subjected to various analyses, including species composition, length-weight relationships for several shrimp species, and identification of shrimp fishing grounds. The results reveal that banana shrimp and yellow shrimp are the predominant species within the catch, both exhibiting negative allometric growth patterns. The fishery’s most productive fishing location is identified in Pantai Village, highlighting this area as a potential focus for sustainable management initiatives. These findings underscore the need for ongoing monitoring and targeted management practices to promote the long-term sustainability of the shrimp fishery in Kotabaru.